Longmire The complete sixth and final season - Raber, Brian J.; Davis, Brad, (R. Bradley); Baldwin, Hunt; Coveny, John; Taylor, Robert, 1963-; Sackhoff, Katee; Phillips, Lou Diamond, 1962-; Freeman, Cassidy, 1982-; Bartley, Adam; Johnson, Craig, 1961-; Netflix (Firm); Warner Horizon Television; et al. (Burbank, CA : Warner Bros. Home Entertainment, 2017)
A Wyoming sheriff struggles to cope with his wife's death as he attempts to move on with his life and career.
Disc 1. Eagle and the osprey ; Fever ; Thank you, Victoria ; A thing I'll never understand -- Disc 2. Burned up my tears ; No greater character endorsement ; Opiates and antibiotics -- Disc 3. Cowboy Bill ; Running eagle challenge ; Goodbye is always implied.
Title from container.
Based upon the "Walt Longmire Mysteries" book series by Craig Johnson.
Wide screen.
Special feature: cast interview.
Robert Taylor, Katee Sackhoff, Lou Diamond Phillips, Cassidy Freeman, Adam Bartley.
Originally broadcast as episodes of the television program in 2017.
Keywords: Longmire, Walt -- (Fictitious character) -- Drama; Longmire, Walt -- (Fictitious character).; Sheriffs -- Wyoming -- Drama; Murder -- Investigation -- Drama; Murder -- Investigation; Sheriffs; Wyoming -- Drama; Wyoming; DVDs; DVD-Video discs; Video recordings; Detective and mystery fiction; Television series; Action and adventure television programs; Detective and mystery television programs; Fiction television programs; Video recordings for the hearing impaired; Detective and mystery television programs; Drama; Fiction television programs; Television series; Video recordings for the hearing impaired; Drama; Crime television programs; Based on the book; Action and adventure television programs; Western television programs; Detective television programs; Mystery television programs; Detective fiction; Mystery fiction